Suicide after reception into prison: A case-control study examining differences in early and late events. - Daniel Radeloff (Public Library of Science (PLoS), 2021)
Objective Prisoners constitute a high-risk group for suicide, with suicide rates about 5 to 8 times higher than in the general population. The first weeks of imprisonment are a particularly vulnerable time, but there is limited knowledge about the risk factors for either early or late suicide events. Methods Based on a national total sample of prison suicides in Germany between 2005 and 2017, suicides within the first 2 (4 and 8) weeks after reception into prison were matched by age and penalty length with cases that occurred later. Factors that potentially influence the timing of suicide were investigated. Results The study has shown that 16.7% (31.5%) of all 390 suicides in German prisons occurred within the first two weeks (two months) of imprisonment. Factors that facilitate adaptation to the prison environment (e.g. prior prison experience) were negatively associated with early suicide events. Factors that hindered the adaptation process (e.g. withdrawal from illicit drugs) were observed more frequently in early suicide events than in late ones. These factors are active at different times of imprisonment. Conclusion At reception, particular attention should be paid to the following factors associated with early suicide events: widowed marital status, lack of prison experience, and drug dependency.